Skepticism and American faith : from the Revolution to the Civil War - Grasso, Christopher (Oxford University Press, 2018)
Between the Revolution and the Civil War, the dialogue of religious skepticism and faith profoundly shaped America. Although usually rendered nearly invisible, skepticism touched-and sometimes transformed-more lives than might be expected from standard accounts. This book examines Americans wrestling with faith and doubt as they tried to make sense of their world.